Validity of Interactive learning PowerPoint Media based on Guided Inquiry on Thermochemistry Topic for Class XI SMA/MA - Rizka Chairani Yasin; Syamsi Aini (Entalpi Pendidikan Kimia, 2022)
Thermochemistry is one of the chemistry learning materials that is difficult for students to understand, so it requires a level of chemical representation in the learning process which is assisted by the presentation of interactive powerpoint media. This study aims to produce an interactive powerpoint learning media based on guided inquiry that is suitable for use for learning and can determine the level of validity of the interactive powerpoint learning media. The type of research used is Research and Development (R&D) with a 4D development model. The research instrument used was a validity questionnaire which was processed using the Aiken's V formula.